Genocias ir rezistencija Nr. 38(2) - Buchaveckas, Stanislovas; Jaskelevičius, Tadas; Balkytė, Dalia; Ėmužis , Marius; Bambals , Ainars; Masiulionytė , Asta (Genocidas ir rezistencija, 2015)
Pilnas leidinys